APPLICATION OF BENFORD’S LAW ON TRADE VOLUME OF CRYPTOCURRENCIES - Alexander, Ann Mary; Beegam. S, Resia (International Journal of Engineering Technologies and Management Research, 2022)
Cryptocurrencies have become a global phenomenon and its trading volume has been increasing since 2017 Aloosh and Li (2019). However, cryptocurrencies have been accused of market manipulation in the past. Benford’s law is widely used for detecting probability of frauds and manipulation in various fields. This study applied Benford’s law on trade volume of cryptocurrencies. Chi- square statistics revealed that except for Cardano and USDT all the other cryptocurrencies did not conform to the distribution and reveals the dataset could have been manipulated. This method may be used as the pre-requisite before doing fine-grain screening such as machine learning and graph-based searching.